A Critical Review on Siddha System and Nano Technology - Manickavasagam, R.; Rajam, C. Senthamil (Technological Innovation in Pharmaceutical Research Vol. 8, 2021)
Nowadays, the name "nanotechnology" conjures up images of a mystical world. Almost all disciplines, such as information technology, civil engineering, and the medical system, are ruled by this growing science. in technological applications. Recent advancements in nanomedical technology are assisting in the detection and treatment of some life-threatening disorders such as cancer and other cellular illnesses. The Siddha system of medicine is one of the world's oldest traditional medical systems. This technique is prevalent throughout South India, particularly in Tamil Nadu. The Siddha system is an ancient medical tradition founded by Siddhars, extraordinary sages. Varmam, Alchemistry, Yogic practices are the some of unique specialties in Siddha system. Biotechnology, Nanotechnology, Biochemistry, Pharmacology, and other modern scientific concepts are abundantly found in the Siddha system. This article discusses nanotechnology concepts in Siddha medical pharmacology, with references to Siddha literature.